Respuesta :

Answer: Choice C) -11

-----------------------------------

Explanation:

The first equation given is y = 3 - 1/2x
In other words, y is the same as 3 - 1/2x. 
We can replace y in the second equation with 3 - 1/2x
This is known as substitution (think of a substitute teacher who is a temporary replacement for your teacher)

Doing this leads to...
3x+4y = 1
3x+4*y = 1
3x+4*( y ) = 1
3x+4*( 3 - 1/2x ) = 1 <<--- y has been replaced with 3-1/2x
3x+4*(3) +4*(-1/2x) = 1
3x+12-2x = 1
3x-2x+12 = 1
x+12 = 1
x+12-12 = 1-12 <<-- subtracting 12 from both sides
x = -11
Which is why the answer is choice C) -11

The system of equations has  value of x equal to  -11 .

What is elimination method?

The elimination method is the process of eliminating one of the variables in the system of linear equations using the addition or subtraction methods in conjunction with multiplication or division of coefficients of the variables.

According to the question

[tex]y = 3 - \frac{1}{2} x[/tex]

[tex]y = \frac{6-x}{2}[/tex]

2y = 6 - x

Putting x and y on left side

x + 2y   = 6 ------------------- (1)

3x + 4y = 1 ------------------- (2)

Now,

solving both equation by elimination method

Multiplying equation (1) by 3

to make equal coefficient for y  

So, y  can be eliminated

3(x + 2y)=6 * 3

3x + 6y = 18 -------------- (3)

Now,

subtracting eq(2)  from (3)

3x + 6y = 18

-3x - 4y = -1  

2y = 17

y = 8.5

Putting value of y in eq(1)

x + 2y  = 6  

x + 17 = 6

x = -11

Hence, The system of equations has  value of x is -11 .

To know more about elimination method here:

brainly.com/question/14619835

#SPJ2

ACCESS MORE